ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS DALAM PROBLEM SOLVING DITINJAU DARI ADVERSITY QUOTIENT - Rohman, Syaifur; Atikurrahman, Atikurrahman; Saiful (FKIP Universitas Islam Jember, 2022)
This qualitative descriptive study aims to analyze mathematical creative thinking skills in problem-solving in terms of the adversity quotient. The study was conducted on 23 third-semester students of the Faculty of Tarbiyah, Ibrahim University. Collecting data using questionnaires, tests, interviews, and documentation. Questionnaire to determine the Adversity Quotient scale. A test to measure mathematical creative thinking skills. Data analysis in the form of induction and reduction theory. The results of the questionnaire showed 6 students (26%) quitters, 14 students (61%) campers, and 3 students (13%) climbers. The test results showed that 8 students (35%) were highly capable, 11 (48%) were moderate, and 4 (17%) were low. The results of the analysis show that the fluency criteria of students with the quitter type meet three problem-solving indicators. Flexibility criteria students with the camper type met all indicators but lacked detail, and originality criteria students with the climber type were able to fulfill all problem-solving indicators in detail. Keywords: mathematical creative thinking, problem-solving, adversity quotient